Comparative Analysis of Temperature Rhythms Based on Distal-Proximal Gradient Skin Temperature in Female Basketball Players and Sedentary Female Students - Nakagawa, Yuki; Tamada, Yoshiki; Murakami, Tomomi; Yamano, Kaoru (International Journal of Basketball Studies, 2023)
BACKGROUND: Athlete’s performances are related to circadian rhythms, and their performance fluctuates depending on the time of day. It is essential to understand the characteristics of an athlete's circadian rhythm in order to achieve the highest performance during a game. METHODS: This study compared the temperature rhythms between 16 nationally-ranked female basketball players (mean age: 20.4 ± 1.1 years) and 18 female students (mean age: 20.2 ± 0.6 years) with no exercise habits in A university. They were collected the date of the distal-proximal skin temperature gradient non-invasively. The temperature rhythms were calculated using the cosinor method. RESULTS: The mesor and amplitude of temperature rhythms did not differ significantly between basketball players and college students (p = 0.261, 0.237, respectively). However, the acrophase of temperature rhythms significantly advanced in basketball players (median; 3:28h, interquartile range; 2:16 - 4:25h) compared to college students (median; 6:00 h, interquartile range; 3:50 – 19:41h) (p = 0.004). The temperature rhythms of several basketball players did not match those of the majority of the team. CONCLUSIONS: To maximize the performance of the team, it might be essential to assess the circadian rhythms based on DPG for each individual basketball player.